Design of Biodegradable Films Using Pecan Nut Cake Extracts for Food Packing - Alves, Jamila dos Santos; Canabarro, Nicholas Islongo; Boeira, Caroline Pagnossim; Melo, Pamela Thais Sousa [UNESP]; Aouada, Marcia Regina de Moura [UNESP]; da Rosa, Claudia Severo (MDPI, 2023)
The excessive consumption of plastic packaging and its consequent disposal and accumulation in the environment have aroused the interest of researchers in developing packaging that can cause less harm to nature. In this sense, this article presents research on the addition of antioxidant extracts from pecan nut cake in biodegradable packaging made with a polymeric mixture of gelatin and corn starch. The films produced were characterized by scanning electron microscopy (SEM), Fourier transform infrared (FTIR) spectroscopy, thickness, mechanical properties, water vapor permeability (WVP), solubility, water contact angle, optical properties, in vitro bioactive activity, and biodegradability. A higher concentration of total phenolic compounds (101.61 mg GAE/g) was found for the condition where alcohol content and extraction time were 65% and 20 min, respectively. Pecan nut cake (PNC(extracts did not influence the film’s tensile strength, and elongation at break was tightly increased by adding 10–20% extracts. The film’s characterization pointed to more than 67% solubility, and adding PNC extract implied more hydrophilic surfaces (contact angles lower than 65°). Furthermore, the film opacity showed a linear relation with PNC extract concentration, and a higher luminosity (L*) was observed for the film without extract. Furthermore, the antioxidant activity of the films was enhanced with the addition of PNC extracts, and complete biodegradation was observed until the ninth day. Therefore, biodegradable films prepared from a mixture of gelatin starch and enriched with PNC extracts showed excellent mechanical properties and potential as carriers of antioxidant compounds, allowing us to propose their use as active packing.
Keywords: biodegradable films; biopolymers; pecan nut cake; phenolic compounds